Sentinel-2 imagery, S6, south-west Greenland, July 2017: Broadband albedo and surface type classification ... - Tedstone, Andrew; Cook, Joseph (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
This dataset consists of (1) broadband albedo calculated using a narrowband-to-broadband approximation and (2) surface type classification into snow, clean ice, light algae, heavy algae, cryoconite and water, as determined by a supervised classification algorithm, as applied to Sentinel-2 overpasses of S6, K-transect, south-west Greenland on 20 and 21 July 2017. Funding was provided by the NERC standard grant NE/M021025/1. ... : Sentinel-2 imagery (European Space Agency) downloaded from Sinergise, Slovenia and converted from L1C to L2A reflectance using ESA Sen2Cor at 20 m resolution. Reflectance data ingested into a Random Forests classifier which was first trained on field data acquired in "Multi-spectral unmanned aerial system imagery, S6, south-west Greenland, July 2017: Levels 2 (ground reflectance) and 3 (broadband albedo and surface type classification)" (DOI: 10.5285/77ca631f-a3a4-4f26-bc90-57bb17baa6fc), in order to generate classification maps of ice sheet surface type across the study area. A narrowband-to-broadband albedo conversion was also applied following Liang (2001, Remote Sensing of Environment). ...